The Relationship Between Leadership Styles and Motivation Level: A Study of Public Bank Berhad Alor Setar - Muhammad, Majid (2010)
This study investigates the relationship between leadership styles of the manager and motivation level of the staff: A study of Public Bank Berhad Alor Setar. A research model was developed based on theories which are Path-Goal Theory by House (1971) and Need Achievement Theory by Atkinson & Birch (1978). The objectives of this study are to examine the relationship between leadership styles and the motivation, and to investigate the most influential leadership style that motivates staff. This study used the quantitative method involving 50 staff of Public Bank Alor Setar. The study revealed that the leadership style of managers, (Supportive, Directive, Participative and Achievement Oriented) factors are not supported and all hypotheses are rejected, namely HI, HIa,Hlb, Hlc,Hld and H2.